IMPLEMENTATION OF MARKET AND PRICE CONCEPTS IN ISLAMIC ECONOMICS PERSPECTIVE: A CASE STUDY OF HORE STORES IN SANGATTA UTARA BASED ON IBN TAYMIYYAH'S THOUGHTS - Djuanda Adhi Nugraha; Silviana Mayang Sari; Dessy Lutfiana Alwi; Tisya Rahma Yeni; Allyiah Allyiah (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: Islamic market principles emphasize fairness, justice, and transparency in economic transactions, reflecting ethical values foundational to Islamic teachings. Spesific Background: In the modern business environment, implementing these principles poses challenges, particularly for small and medium enterprises (SMEs) striving to balance ethical standards with market competitiveness. Knowledge Gap: Limited research exists on the practical application of Islamic economic principles in contemporary business contexts, especially within local SME settings. Aims: This study investigates how Toko Hore, a business in Sangatta Utara, implements Islamic market principles, drawing from Ibn Taymiyyah's economic thoughts. Results: Findings indicate that Toko Hore incorporates key elements of fairness, justice, and transparency in its operations. However, it encounters obstacles in maintaining these principles amidst the pressures of modern market dynamics. These challenges include limited resources, consumer preferences, and competitive pressures. Novelty: This research uniquely bridges classical Islamic economic theories with real-world applications in the SME context, offering fresh perspectives on the adaptability of ethical principles in modern commerce. Implications: The study provides valuable insights for businesses and policymakers aiming to integrate Islamic economic principles into contemporary market frameworks, highlighting the need for innovative strategies to overcome practical challenges.